2021
DOI: 10.1159/000518444
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Rare Association of Diffuse Thyroid Lipomatosis with Amyloid Deposition

Abstract: Diffuse thyroid lipomatosis is a rare histopathological condition of unknown etiology, characterized by diffuse fatty infiltration of the thyroid stroma, which can result in diffuse goiter with compressive symptoms. We report a case of a 46-year-old man with 1-year history of progressive goiter enlargement with compressive symptoms. Imaging studies revealed multiple coalescent nodules. The patient underwent surgery, and the microscopic appearance revealed a diffuse infiltration of thyroid stroma by mature adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Coca-Pelaz et al [ 9 ] and Nessim et al [ 10 ] reported a papillary thyroid carcinoma within an amyloid goiter due to primary amyloidosis. As in our case, most patients with amyloid goiter present with an enlarged thyroid gland, usually bilateral and diffuse, which can rapidly progress over weeks to months [ 3 , 4 , 9 ] and it can be associated with compressive symptoms such as dysphagia, dysphonia, and dyspnea [ 4 , 9 , 10 ]. Thyroid function is usually normal [ 3 , 4 , 7 , 9 , 10 ], but a minority of patients have hyper- or hypo-thyroidism [ 14 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Coca-Pelaz et al [ 9 ] and Nessim et al [ 10 ] reported a papillary thyroid carcinoma within an amyloid goiter due to primary amyloidosis. As in our case, most patients with amyloid goiter present with an enlarged thyroid gland, usually bilateral and diffuse, which can rapidly progress over weeks to months [ 3 , 4 , 9 ] and it can be associated with compressive symptoms such as dysphagia, dysphonia, and dyspnea [ 4 , 9 , 10 ]. Thyroid function is usually normal [ 3 , 4 , 7 , 9 , 10 ], but a minority of patients have hyper- or hypo-thyroidism [ 14 ].…”
Section: Discussionmentioning
confidence: 78%
“…As in our case, most patients with amyloid goiter present with an enlarged thyroid gland, usually bilateral and diffuse, which can rapidly progress over weeks to months [3,4,9] and it can be associated with compressive symptoms such as dysphagia, dysphonia, and dyspnea [4,9,10]. Thyroid function is usually normal [3,4,7,9,10], but a minority of patients have hyper-or hypo-thyroidism [14]. As previously stated, our patient had normal levels of T4, T3, and TSH.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Amyloid goiter is described as an accumulation of amyloid, an amorphous proteinaceous material, in the thyroid gland in sufficient amounts to cause an increase in the size denotes amyloid goiter [ 1 ]. In occasional cases, the accumulation of fat coexists with the deposition of amyloid [ 2 ]. Although amyloid deposition in the thyroid is relatively common, a clinically significant enlargement due to its accumulation is rare.…”
Section: Introductionmentioning
confidence: 99%